Numerical aspects of fluid infusion inside a compressible porous medium undergoing large strains - Celle, Pierre; Drapier, Sylvain; Bergheau, Jean-Michel (European Journal of Computational Mechanics, 2008)
A new model for a thermo-reactive fluid flow across a highly compressible porous medium has been proposed and employed to predict infusion-based manufacturing processes for polymer composites (Celle, 2006). These techniques consist in mixing the reinforcements and the resin during the manufacturing cycle, transversely to the fabrics plane, by applying a pressure on the resin/preform stacking. This yields cost reductions and avoids filling problems. The introduction of a numerical model in a finite element software to study infusion-based processes will increase their diffusion by a reliable prediction of both part thickness and porosity (Celle et al., 2008). The present paper deals mainly with the numerical treatments related to the resin layer.